Pembentukan Karakter Siswa dan Profesionalisme Guru Melalui Budaya Literasi Sekolah - Baharuddin Baharuddin (El-Idare, 2017)
This article aims to reveal and reinforce the importance of cultural literacy at school turn. This article uses literature study to assess the literacy issues in depth. The study showed that reviving the school literacy culture can be capital in improving the competence of students and teachers, assist in the formation of student character, and improve the professionalism of teachers and can deliver effective schools into schools.